Aortic flow patterns by 4D flow CMR in Marfan and Loeys-Dietz patients before and after valve sparing aortic root replacement: a comparison with healthy volunteers. (3rd October 2022) - Ruiz Munoz, A; Guala, A; Dux-Santoy, L; Rodriguez-Palomares, J F; Garcia-Duran, A; Garrido-Oliver, J; Galian-Gay, L; Valente, F; Casas, G; Fernandez-Galera, R; Johnson, K; Wieben, O; et al.
Abstract: Introduction: Abnormal aortic flow patterns in patients with a connective tissue disorder (CTD), such as Marfan or Loeys-Dietz syndrome, may contribute to aortic root dilation [1, 2]. Valve sparing aortic root replacement, which is effective in reducing the risk of aortic dissection in case of severe dilation, may also normalize flow patterns beyond the replaced aorta and potentially slow its progressive aortic dilation. Purpose: To assess aortic flow dynamics in patients with a CTD by 4D flow cardiovascular magnetic resonance (CMR) before and after valve sparing aortic root replacement, and to compare the results with those of healthy volunteers (HV). Methods: Patients with Marfan or Loeys-Dietz syndrome underwent two non-contrast enhanced 4D flow CMR, one before and another after undergoing valve sparing aortic root replacement. Healthy volunteers matched for age, sex and BSA were also included for comparison. Maximum velocity, in-plane rotational flow (IRF), systolic flow reversal ratio (SFRR) and wall shear stress (WSS) magnitude and its axial and circumferential components were obtained at 24 planes covering the thoracic aorta from the sinotubular junction to the descending aorta at the diaphragmatic level [3–5]. Results: Sixteen patients and 21 healthy volunteers were included. Demographic and clinical data is presented in Table. The mean time between the CMR prior and posterior to surgery was 15 months. Compared to HV, patients with CTD before intervention presented lower maximum velocity at the proximal ascending aorta (Fig. 1A), lower IRF and circumferential WSS at the arch and the proximal descending aorta (Fig. 1B and F), lower magnitude and axial WSS at the proximal ascending and descending aorta (Fig. 1E and D), and increased SFRR at the proximal descending aorta (Fig. 1C). The intervention completely restored maximum velocity and partially-restored physiological helical flow and circumferential WSS, but barely improved axial WSS and SFRR. Conclusion: Valve sparing aortic root replacement in patients with Marfan or Loeys-Dietz syndrome partially restore to physiological level both in-plane rotational flow and circumferential wall shear stress in the descending aorta. This flow normalization may contribute to prevent progressive dilation after the surgery. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III (Spain) (PI17/00381)Spanish Society of Cardiology (SEC/FEC-INV-CLI 20/015)